Digital Readiness Assesment to Improve Quality of Life Using SWOT Analysis: Case Study for Natuna Regency Area - Rizkia, Irma (Bina Nusantara University, 2025)
Natuna Regency, as an outlying region, faces challenges in enhancing its digital readiness to effectively implement digital transformation. Currently, the digital readiness of the region remains at the survival level. This research aims to explore the most effective strategies in improving the digital readiness of the city government, and its impacts on public services and community participation. An empirical approach is employed through a case study in Natuna Regency. The research begins with a literature review and a pilot case study on the digital readiness of a region, validated through questionnaires based on the Garuda Digital Transformation Framework (GDTF) developed by ITB as the basis for measuring digital readiness in Natuna Regency. SWOT analysis is utilized to provide strategies for Natuna Regency. The digital transformation readiness of Natuna Regency is at the survival level, with a score of 60.37. Tangible impacts of digital transformation are evident in the business processes conducted by government agencies and the ecosystem of governance and society in Natuna Regency. The primary recommendation is to leverage internal strengths to address external challenges and capitalize on opportunities in the digital transformation era. Strategies include leveraging high digital literacy, understanding data security, developing technological infrastructure, enhancing human resource skills, and collaborating with the private sector and educational institutions. By integrating these strategies, Natuna Regency can more effectively respond to technological challenges and leverage digital transformation opportunities for sustainable progress.